ROLE OF LECTIN-SUBSTRANCE RECOGNITION IN IMMUNOREGULATORY INTERACTION BETWEEN INTERLEUKIN-2 IGG - S. M. Sobolev; T. N. Nikolaeva; E. A. Grigorjeva; A. V. Pronin (Медицинская иммунология, 2014)
As assessed by decreased response of ConA-induced blasts to IL-2, a staphylococcal protein A was shown to extract IL-2 from cultural medium after its preincubation with IgG, but it did not bind pure IL-2. Normal human immunoglobulin inhibits reaction of DTH effectors to Listeria antigen, which is also IL-2-dependent. An immunomodulating drug Phosprenyl (sodium polyprenylphosphate) abolishes the inhibitory ffect of immunoglobulin. Since Phosprenyl (as shown earlier) interacts with alpha-chain of rIL-2 and blocks IL-2 activity, the two drugs are in competitive relations. The latter may be explained by identities in prostetic carbohydrate groups of the both glycoproteins (CD25 and immunoglobulin), whereas Phosprenyl and IL-2 would behave like as lectins. These results characterize local conditions and mechanisms of immune regulation under tissue domination of gamma-globulin or antibodies of a given isotype. IgG binds with IL-2, reacting not with an active center but with effector region of IgG molecule, thus blocking IL-2 activity. Since a similar effect is observed under in vivo conditions (in a DTH model), the phenomenon revealed may explein inhibition of immune response after passive injection of antibodies, as well as a feed-back relationship between humoral and cellular immunity. Inhibition of IL-2 biological activity after its interaction with IgG and immune complexes may be considered as a universal mechanism of immune regulation performed by a feedback regulation, which may be influenced by means of Phosprenyl-like immunomodulators. In some infections, malignant growth etc., such mechanism may be of utmost pathogenetic significance. Moreover, such a mechanism cannot be also excluded in some physiological immunogenetic interactions, e.g., in feto-maternal system, where it could promote a positive selection for individuals with broader MHC repertoire, which would be necessary for development of individual and population-based resistance to infections